New product development from inactive problem perspective in Indonesian SMEs to open innovation - Rony Prabowo; Moses Laksono Singgih; Putu Dana Karningsih; Erwin Widodo (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
New product development is an important innovation that should be done to meet consumers' new trends. This paper is prominent as it discusses new product development through the inactive problem perspective in SMEs in Indonesia as a way to explore customers' expectations, which are often challenging to analyze. The capability to develop a new product based on the inactive problem perspective allows SMEs to become pioneers that possess various competitive advantages, including strong brand awareness. This study included 14 samples of SMEs to represent the characteristics of SMEs in Indonesia between 2016 and 2018. We used the particle swarm optimization approach for the decision making of several SME parameters with the profit maximization function. This paper is the first paper to discuss the relationship between the cost of ideas and production costs in the types of SMEs with an inactive problem perspective in Indonesia to obtain maximum profits by considering various factors that affect the costs and revenue of SMEs. This paper also analyzes the cost used for an idea realization to get maximum profit. This study shows that differences were found in each type of SME, and these difference were related to the amount of funds that were used to explore, realize, and make a profit out of a specific idea.
Keywords: 650; product; development; inactive; problem; SME; maximum profit